2017
DOI: 10.1039/c7fd00108h
|View full text |Cite
|
Sign up to set email alerts
|

Halogen effects on the solid-state packing of phenylalanine derivatives and the resultant gelation properties

Abstract: Phenylalanine is an important amino acid both biologically, essential to human health, and industrially, as a building block of artificial sweeteners. Our interest in this particular amino acid and its derivatives lies with its ability to form gels in a number of solvents. We present here the studies of the influence of halogen addition to the aromatic ring on the gelation properties and we analyse the crystal structures of a number of these materials to elucidate the trends in their behaviour based on the hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…On the other hand, the gelation ability is also highly influenced by properties such as solubility and polarity [ 16 , 17 , 18 ]. Slight variations on the polarity of the gelator may either improve or reduce its gelling ability depending on the solvent used for the process [ 14 , 19 , 20 ]. Several works reported the influence of fluorine on the physical properties and self-assembly ability of different types of compounds [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the gelation ability is also highly influenced by properties such as solubility and polarity [ 16 , 17 , 18 ]. Slight variations on the polarity of the gelator may either improve or reduce its gelling ability depending on the solvent used for the process [ 14 , 19 , 20 ]. Several works reported the influence of fluorine on the physical properties and self-assembly ability of different types of compounds [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a mixture of MA and ADPE can be applied as a low molecular weight gelator for less polar solvents, such as 1,2-dichloroethane . The electron-withdrawing halogen atom may further enhance the gelation ability. Higher selectivity for the ( S )-salt was observed when crystallized from dioxane or acetone and the efficiency increased to 0.83 (entries 6–7). On the other hand, the ( R )-salt was preferentially obtained via crystallization from water (entry 1) although the efficiency was not high.…”
Section: Resultsmentioning
confidence: 99%
“…The latter was expected to bring a supplementary possibility of π–π stacking interactions 46 . In order to evaluate the existence, the extent and the influence of potential π–π stacking interactions, two lysine derivatives were synthesized which differed by the presence of one chlorine atom substituting the ortho position of the aromatic ring (in compound 7 ) 47–50 . The carboxylic acid group was left unmodified so as to contribute to the ability to establish hydrogen bonds and keep water solubility high enough.…”
Section: Resultsmentioning
confidence: 99%